2012
DOI: 10.1017/s0003055412000093
|View full text |Cite
|
Sign up to set email alerts
|

The Missionary Roots of Liberal Democracy

Abstract: T his article demonstrates historically and statistically that conversionary Protestants (CPs) heavily influenced the rise and spread of stable democracy around the world. It argues that CPs were a crucial catalyst initiating the development and spread of religious liberty, mass education, mass printing, newspapers, voluntary organizations, and colonial reforms, thereby creating the conditions that made stable democracy more likely. Statistically, the historic prevalence of Protestant missionaries explains abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
229
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(236 citation statements)
references
References 137 publications
(182 reference statements)
7
229
0
Order By: Relevance
“…A new twist is brought in by Doepke and Zilibotti (2008) who examine the evolution of Protestant values in interaction with occupational choice. More broadly, Woodberry (2012) provides evidence for the relationship between religious missions and democracy and argues that Protestants played an important role for modernization in general with support of mass education being one important mechanism. of the death penalty is generally associated with conservatism.…”
Section: Introductionmentioning
confidence: 99%
“…A new twist is brought in by Doepke and Zilibotti (2008) who examine the evolution of Protestant values in interaction with occupational choice. More broadly, Woodberry (2012) provides evidence for the relationship between religious missions and democracy and argues that Protestants played an important role for modernization in general with support of mass education being one important mechanism. of the death penalty is generally associated with conservatism.…”
Section: Introductionmentioning
confidence: 99%
“…He mentioned that there was an emerging body of scholarship that supported global faith-based interventions on education, religious liberty and social democracy. 7 He referenced Lewis Rambo's work on metrics of spiritual transformation. 8 As the Lausanne Covenant states, "Presence is indispensible-serving the hurting, saving the lost."…”
Section: The Line In the Sandmentioning
confidence: 99%
“…Woodberry found that the missionary movement had strong, positive influence on liberal democratization. Countries open to missionaries ended up upholding democratic principles and experienced democratic government significantly more so that countries not exposed to missionaries [60]. In another perspective on proselytization, Dena Freeman explains how the Pentecostal movement in Africa seeks to transform individual converts, helping them to break away from traditional cultural norms, thereby liberating themselves to pursue wealth and personal progression [61].…”
Section: The Issue Of Proselytizationmentioning
confidence: 99%